Correlation between external respiratory indicators and amino acid composition of blood in athletes - Pavlov, V.A.; Rogov, O.S.; Doronin, A.I. (Theory and Practice of Physical Culture, 2022)
Objective of the study was to identify the role of amino acids in the formation of the specific signs of the structural trace of adaptation. Methods and structure of the study. The tidal volume rates were obtained by means of spirometry, including inspiratory and expiratory reserve volumes (RVinsp, RVexp) and actual vital capacity; by means of morphometry - predicted vital capacity, maximum tidal volume under loads, respiratory minute volume, maximum and specific tidal volume (per Watt of energy), as well as PWC170, specific PWC170 and critical specific power (specific power, at which the respiratory function efficiency is reduced). Results and conclusions. Branched-chained amino acids (their relative content) in the wrestlers have a comprehensive effect on the external respiration function. The critical specific power in the hockey players positively correlates with the absolute glycine level and negatively - with the absolute taurine (TAU) level. In addition, there is a positive correlation with the relative glutamine and arginine levels. Therefore, the identified difference in the amino acid composition of the athletes’ blood is accompanied by different correlation relationships between the external respiratory indicators. It should be noted that it is ancient amino acids that have the largest number of such correlations - in representatives of all sports. The wrestlers were found to have more correlations with the absolute content of amino acids, and the hockey players have more correlations with the relative content of amino acids. The data obtained can be used as a marker for the athletes’ training level.